Thermostress. An automatic imaging process for assessing plant water status from thermal photographs - Jiménez-Bello M.A.; Ballester C.; Castel J.R.; Intrigliolo D.S. (The use of remote sensing and geographic information systems for irrigation management in Southwest Europe, 2012)
Leaf temperature can be used for monitoring plant water status. Nowadays, by means of thermography, canopy temperature can be remotely determined. In this sense, it is crucial to automatically process the images. In the present work, a methodology for the automatic analysis of frontal images taken on individual trees was developed. The camera used in this investigation took at the same time thermal and visible scenes, so it was not necessary to overlap the images. During the processing in batch no operator participated. This was done by means of a non supervised classification of the visible image from which the presence of sky and soil was detected. In case of existence, a mask was performed for the extraction of intermediated pixels to calculate canopy temperature by means of the thermal image. Sunlit and shady leaves could be detected and isolated. Thus, the procedure allowed to separately determine canopy temperature either of the more exposed part of the canopy or of the shaded portion. The methodology developed was validated using images taken in several regulated deficit irrigation trials in persimmon and two citrus trees cultivars (Clementina de Nules and Navel Lane-Late). Overall, results indicated that similar canopy temperatures were calculated either by means of the automatic process or the manual procedure. In addition, differences in midday stem water potential and stomatal conductance among irrigation treatments were associated with differences in canopy temperature in persimmon trees. The procedure here developed here allowed to drastically reduce the time amount used for image analysis also considering that no operator participation was required. Indeed, the tool here proposed will facilitate further investigations in course for assessing the feasibility of using thermography for detecting plant water status in woody perennial crops with discontinuous canopies.